Autologous Stem Cell Transplantation for Children With Renal Tumors, and Adults With Wilms Tumor: Retrospective Analysis of the Japanese Transplant Registry Unified Management Program. Issue 4 (3rd May 2020) - Kobayashi, Ryoji; Inoue, Masami; Takahashi, Yoshiyuki; Kikuta, Atsushi; Ogawa, Atsushi; Koga, Yuhki; Koh, Katsuyoshi; Hashii, Yoshiko; Hara, Junichi; Kato, Koji; Tabuchi, Ken; Matsumoto, Kimikazu
Abstract : Background: Almost all pediatric patients with renal tumors are diagnosed with nephroblastoma (Wilms tumor), clear cell sarcoma, or malignant rhabdoid tumor. The choice of treatment is important for relapsed and refractory patients with nephroblastoma. Furthermore, clear cell sarcoma of the kidney (CCSK) and malignant rhabdoid tumor of the kidney (MRTK) have a poor prognosis compared with nephroblastoma. Thus, stem cell transplantation (SCT) is sometimes selected to treat these tumors. Patients and Methods: The authors targeted a total of 84 patients with nephroblastoma, CCSK, and MRTK who underwent a first autologous SCT between 1992 and 2014, and were registered in the Japanese Transplant Registry Unified Management Program system. The authors retrospectively analyzed the SCT data for survival rate. Results: Five-year overall survival rates for nephroblastoma, CCSK, and MRTK were 72.4%±6.3%, 46.8%±13.8%, and 36.4%±14.5%, respectively. The event-free survival rates at 5 years were 64.9%±6.7%, 35.7%±12.8%, and 27.3%±13.4%, respectively. The relapse rates at 5 years were 25.3%±11.4%, 46.2%±28.4%, and 60.0%±43.1%, respectively. Conclusion: Although the survival rate for nephroblastoma was relatively high, those of CCSK and MRTK were poor.